2017
DOI: 10.1073/pnas.1711406115
|View full text |Cite
|
Sign up to set email alerts
|

LAMOST telescope reveals that Neptunian cousins of hot Jupiters are mostly single offspring of stars that are rich in heavy elements

Abstract: We discover a population of short-period, Neptune-size planets sharing key similarities with hot Jupiters: both populations are preferentially hosted by metal-rich stars, and both are preferentially found in systems with single-transiting planets. We use accurate Large Sky Area Multi-Object Fiber Spectroscopic Telescope (LAMOST) Data Release 4 (DR4) stellar parameters for main-sequence stars to study the distributions of short-period [Formula: see text] planets as a function of host star metallicity. The radiu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
70
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 60 publications
14
70
1
Order By: Relevance
“…This is consistent with trends observed by Mulders et al (2016) and Dong et al (2018), who studied the host star metallicities for samples of 665 and 295 planets, respectively. Both studies used spectroscopically constrained metallicities from LAMOST.…”
Section: Metallicity and The Prevalence Of Short-period Planetssupporting
confidence: 91%
See 2 more Smart Citations
“…This is consistent with trends observed by Mulders et al (2016) and Dong et al (2018), who studied the host star metallicities for samples of 665 and 295 planets, respectively. Both studies used spectroscopically constrained metallicities from LAMOST.…”
Section: Metallicity and The Prevalence Of Short-period Planetssupporting
confidence: 91%
“…Mulders et al (2016) analyzed the LAMOST metallicities and a sample of 665 planet candidates, and found that the occurrence rate of hot small planets (P<10 days, R P < 4 R Å ) is three times higher among super-solar metallicity hosts compared to sub-solar hosts. Dong et al (2018) also analyzed LAMOST metallicities and a sample of 295 planets and reported a similar trend, also noting that hot Neptune-size planets are typically single.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…New observations provide us with the opportunity to characterize the super-Earth and sub-Neptune populations as a function of their host star properties (e.g., Petigura et al 2018;Dong et al 2018). This opens new avenues to investigate and contrast possible signatures the core-powered mass-loss mechanism and photoevaporation imprint on the exoplanet population (e.g., Owen & Murray-Clay 2018;Wu 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Some planets may be much more massive, with high molecular-weight envelopes that resist escape to space. They could be the result of catastrophic escape of the H-He envelopes of close-in giant planets ("hot Jupiters") that have shrunk to Neptune size (Dong et al 2018). The mass of these planets can be measured by precision radial velocity measurements (e.g., Espinoza et al 2016).…”
Section: Introductionmentioning
confidence: 99%